Haggai, Zechariah, Malachi - Redditt, Paul L. (Grand Rapids, MI Eerdmans, 1995)
Includes bibliographciaql references and indexes.
Keywords: Bible O.T. Haggai -- commentaries; Bible. O.T. Zechariah -- commentaries; Bible. O.T. Malachi -- commentaries